The Impact of Formal Institutions on Knowledge Economy - Antonio R. Andrés; Simplice A. Asongu; Voxi S. H. Amavilah (African Governance and Development Institute (AGDI), 2013)
Using Kauffman, Kraay, and Mastruzzi governance indicators, this article analyzes the impact of formal institutions on the knowledge economy- by assessing how the enforcement of Intellectual Property Rights (IPRs) through good governance mechanisms affects the knowledge economy. The article also employs the World Bank's four components of the knowledge economy index characteristic of its knowledge for development (K4D) framework. We estimate panel data models for 22 Middle East & North African and Sub-Sahara African countries over the period 1996-2010. The results show that for this group of countries the enforcement of IPR laws (treaties), although necessary, is not a sufficient condition for a knowledge economy. The results also suggest that other factors are more likely to determine the knowledge economies of these nations. Overall these findings have important implications for both policy and further research.
Keywords: O10; O34; O38; P00; P48; 330; Formal institutions; Knowledge economy; Panel data; Principal component analysis (PCA)